Transformasi komunitas misi: Gereja sebagai ciptaan baru dalam Roh Kudus - Salurante, Tony; Bilo, Dyulius Th.; Kristanto, David (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2021)
Transformation is the key to the growth of the church and mission. Transformation is a positive change toward Christ that marks believers’ life, as indicated by Paul’s exhortation in Romans 12:2. The church refers to the people who believe in Christ so they are renewed by the power of the Holy Spirit. That transformation or renewal empowers the church to function as the light of the world, as a missional community through the power of the Holy Spirit. This article seeks to present the strong correlation between the spiritual transformation of the church by the power of the Holy Spirit with her function as a missional community. This article elaborates the meaning of transformation in the New Testament, the meaning of transformation from the perspective of systematic theology, and the strong correlation between spiritual transformation and the function of the church as a missional community. Abstrak Transformasi adalah kunci dari pertumbuhan gereja dan misi. Hal tersebut merupakan perubahan positif yang menjadi ciri kehidupan orang percaya kearah Kristus, sebagaimana nasehat Paulus dalam Kitab Roma 12:2. Gereja adalah orang-orang yang percaya kepada Kristus sehingga dibaharui oleh kuasa Roh Kudus. Transformasi atau pembaharuan tersebut merupakan hal yang memampukan Gereja untuk berfungsi sebagai terang dunia, sebagai komunitas misional oleh kuasa Roh Kudus. Artikel ini melihat relasi yang erat antara transformasi Gereja oleh kuasa Roh Kudus dengan berfungsinya Gereja sebagai suatu komunitas misi. Artikel ini memaparkan makna transformasi spiritual di dalam Perjanjian Baru, makna transformasi spiritual dari perspektif teologi sistematika, dan relasi erat antara transformasi spiritual dengan fungsi Gereja sebagai suatu komunitas misi.